PRODUCTIVITY GROWTH, TECHNICAL PROGRESS AND EFFICIENCY CHANGE - Kanika Aggarwal, Puneet Singh, (EPRA International Journal of Environmental Economics, Commerce and Educational Management (ECEM), 2022)
This paper analyzes productivity growth of GDP in 5 countries over the period 1990- 2015. The proposed approach relies on using a stochastic production function to provide estimates of technical efficiency, technical change and Total factor productivity.